RISK MANAGEMENT IMPLEMENTATION STRATEGY THROUGH DIVERSIFICATION AT BANK MUAMALAT IN INDONESIA - Rusdi, Muhammad; Diem, M. Junestrada; Pamuji (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
Strategy is of course needed to face risks in every bank, both conventional and sharia banks. One strategy that can be implemented is diversification. Diversification is a financial strategy by placing funds in various investment tools with very different levels of risk and potential profits, and usually this strategy allocates assets. This research examines the strategies used by Bank Muamalat in dealing with/responding to problems that occur. The research results show that one of the strategies carried out by Bank Muamalat is to emphasize its risks through diversification. The financing diversification strategy implemented by Bank Muamalat is to produce healthy financing growth. So that Bank Muamalat makes improvements in end-to-end procedures and maintains the quality of financing by determining risks that will occur. The method used in this research is a qualitative method with a literature study approach. The data used is secondary data, namely data sourced from existing literature and references, such as in journals, scientific papers, encyclopedias and other data sources related to the research topic. Data analysis was carried out in three stages, namely, data reduction, data presentation and verification. This research needs to be carried out because the aim of diversifying is to get as much profit as possible and avoid the threat of loss. Especially at Muamalat Bank, which currently has a lot of competitors, so the bank must be able to manage the losses that it fears will occur in the future. However, of course the strategy carried out is not only diversification, but of course a fairly strong strategy is also needed in Bank Muamalat's risk management. There are things that need to be done, such as identifying risks that will occur, measuring risks that might occur, and how to manage risks that are occurring.